Origins of B-type stars at high Galactic latitudes based on abundances and kinematics. Issue 1 (22nd December 2022) - Liu, Zhicun; Cui, Wenyuan; Zhao, Gang; Liu, Chao; Luo, Changqing; Alexeeva, Sofya
ABSTRACT: The spectral analysis and kinematic studies of faint blue stars of O and B types above the mid-plane of the Milky Way can lead to a better understanding of their populations and origins. In this paper, we present an analysis of the chemical composition and kinematics of 17 B-type stars. Our sample includes 13 B-type stars with | Z | > 0.5 kpc and | b | ≥ 20°, three B-type stars with | Z | ≤ 0.5 kpc and | b | < 20°, and a hot post-asymptotic giant branch (post-AGB) star without infrared excess, in the Milky Way. Our analysis rests on medium-resolution spectra and non-local thermodynamic equilibrium tlusty model atmospheres. The ages and masses of the stars are obtained using solar-metallicity PARSEC isochrones, and we calculate their velocities and Galactic trajectories using galpy and data from the Gaia EDR3. The larger projected rotational velocities and results of abundance analysis of 16 B-type stars indicate that they are likely to be B-type stars of normal Population I. The three B-type stars with | Z | ≤ 0.5 kpc and | b | < 20° can be formed in the Galactic disc. The origins of the 13 B-type stars with | Z | > 0.5 kpc and | b | ≥ 20° are as follows. (i) Analysis of the C and Mg abundances, kinematics and orbits show that 10 of them originate in the Galactic disc at different Galactocentric distances. They may be scattered from the disc via the binary ejection mechanism or the dynamical ejection mechanism. (ii) The three stars presenting abnormal C or Mg abundances and counter-rotating V ϕ might be post-AGB stars accreted from a disrupted satellite of the Milky Way.